The Influence of Microdeletions and Microduplications of 16p11.2 on Global Transcription Profiles. (December 2015) - Kusenda, Mary; Vacic, Vladimir; Malhotra, Dheeraj; Rodgers, Linda; Pavon, Kevin; Meth, Jennifer; Kumar, Ravinesh A.; Christian, Susan L.; Peeters, Hilde; Cho, Shawn S.; Addington, Anjene; Rapoport, Judith L.; et al.
Copy number variants (CNVs) of a 600 kb region on 16p11.2 are associated with neurodevelopmental disorders and changes in brain volume. The authors hypothesize that abnormal brain development associated with this CNV can be attributed to changes in transcriptional regulation. The authors determined the effects of 16p11.2 dosage on gene expression by transcription profiling of lymphoblast cell lines derived from 6 microdeletion carriers, 15 microduplication carriers and 15 controls. Gene dosage had a significant influence on the transcript abundance of a majority (20/34) of genes within the CNV region. In addition, a limited number of genes were dysregulated in trans . Genes most strongly correlated with patient head circumference included SULT1A, KCTD13, and TMEM242 . Given the modest effect of 16p11.2 copy number on global transcriptional regulation in lymphocytes, larger studies utilizing neuronal cell types may be needed in order to elucidate the signaling pathways that influence brain development in this genetic disorder.